KARAKTERISTIK PASIEN LIMFADENITIS TUBERKULOSIS DI KOTA MEDAN TAHUN 2019 - RATNA SAIDAH; HUMAIRAH MEDINA (LP2MTBM MAKARIOZ, 2021)
Tuberculosis is a contagious infectious disease caused by Mycobacterium tuberculosis which attacks the lungs and organsoutside the lungs which is commonly called extrapulmonary TB. Extrapulmonary TB can occur in various organs, but themost common case of extrapulmonary TB is TB lymphadenitis which is an inflammation of the glandular sap commonlyoccurs in the neck, this is the result of MTB activity.This study aims to look at Tuberculosis Lymphadenitis patients in the cityof Medan in 2019 based on gender, age, and BTA examination. This study was a retrospective descriptive study with 30respondents of tuberculosis lymphadenitis patients who were seen from the medical records of the frequency distributioncategory of each variable expressed in proportion. It was found that tuberculosis lymphadenitis patients were more inwomen (20 people). In the largest age range, there were 14 people aged 12- 25 years (46.7%) and all of the BTA werenegative.